Mediating effects of meaning in life on the relationship between family care, depression, and quality of life in Chinese older adults - Zhou, Jing-Jing; Zhang, Yu; Ren, Qing-Zhuo; Li, Ting; Lin, Gui-Ding; Liao, Min-Yi; Chen, Shao-Hua; Tong, Pei; Gao, Yu-Lin (Frontiers in Public Health, 2023)
Background The study explored sources of meaning in older adults and the action path among family care, meaning in life, quality of life, and depression. Materials and methods We investigated 627 older adults using the Sources of Meaning in Life Scale for the Elderly (SMSE), the Family Care Index (APGAR), the Center for Epidemiological Studies Depression Scale-10 (CES-D-10), and the EuroqOL-5 Dimensions (EQ-5D). Results Scores categorized 454 older adults with good family function, 99 with moderate, and 47 with severe family dysfunction; 110 older adults had depression. The structural equation model showed that family care affected the quality of life and depression by influencing meaning, and depression had a significant negative effect on the quality of life (P < 0.05). The model was a good fit for the data (χ2/df = 3.300, SRMR = 0.0291, GFI = 0.975, IFI = 0.971, TLI = 0.952, CFI = 0.971, RMSEA = 0.062). Conclusion Meaning in life is an intermediary factor that affects depression and quality of life in older adults. Family care had a significant positive impact on SMSE and a negative influence on depression. The SMSE effectively clarifies the sources of meaning in life and can be used to improve meaning and promote mental health in older adults.